Soybean Opportunity as Source of New Energy in Indonesia - Muchlish Adie, M.; Krisnawati, Ayda (International Journal of Renewable Energy Development, 2014)
These last few years, the name of soybeans soared as a source of biodiesel. Soy biodiesel is an alternative fuel produced from soybean oil. Soybean potential as an alternative renewable energy source because it is expected to have the highest energy content compared to other alternative fuels. Opportunities to develop biodiesel using soybean oil in Indonesia is quite large, considering the soybean is a commodity that is already known and widely cultivated almost in all over Indonesia. In addition, the use of soybean for biofuel feedstock is expected to motivate farmers to cultivate soybeans, so their use is not limited to non-energy raw materials. Soybean varieties that have a high oil content as well as high yield is a source of major biodiesel feedstock. From 73 soybean varieties that have been released in Indonesia, has an average oil content of 18%. Varieties with high oil content can be used as raw material for biodiesel. Research on the use of soy as an ingredient of energy crops (biodiesel) have been carried out. In fact, soybean oil is the vegetable oil feedstock for most of the biodiesel being produced in the United States today. With the potential for soybean crops in Indonesia, both in terms of availability of land and varieties, the use of soybean oil for biofuel development in Indonesia is the flagship prospective materials for bio fuel substitute than other plants in the future.